CIMAvax-EGF®, new therapeutic alternative for lung cancer: its application in Cienfuegos - Yoana Herrera Leiva; Teresita Sabatés Llerandi (Revista Finlay)
In 2016, the EGF-Predictor Phase IV Clinical Trial Opening Workshop was held in Cienfuegos, sponsored by the Center for Molecular Immunology of Havana which coexist with other clinical trials. The overall objective of the study is to evaluate the safety and efficacy of the CIMAVAX-EGF therapeutic vaccine for the treatment of patients diagnosed with lung cancer in advanced stages of the disease and, within its specific objectives, to assess overall survival and the treated patients’ life quality.